The economics of the developing countries - Myint H. (London : Hutchinson, 1973)
The book provides an examination of the concept of economic growth; the various aspects of initiating the growth process in the agricultural sector; the problems associated with capital requirements, international trade, balanced industrial growth.
Includes bibliographical footnotes and index.
lje 03/10/2018
Loans
Keywords: Economic development; Developing countries